Control of Anxiety Responses in College Students in Situations Of Oral Presentations (Brazilian Journal of Behavioral and Cognitive Therapy, 2004)
The present study had the objective of reducing excessive anxiety in college students during oral presentations in the classroom. It is known that excessive anxiety causes great discomfort and has negative consequences on academic performance and that it might lead to school evasion. Five female university students, 20 to 40 years old, from various courses, participated in the research. The level of anxiety of each participant was evaluated through three measures: (a) Fear of Negative Evaluation (FNE); State-Trait Anxiety Inventory (STAI); and (c) Measure of Hearth Beat Frequency in structured settings. Experimental control was achieved using a Multiple Baseline Between Subjects Design. The intervention included various procedures: Lectures and readings of academic texts, relaxation training, breathing exercises, cognitive restructuring, training in social skills with emphasis in skills for public presentations and social approval of adherence to the therapist's recommendations. The procedures helped to reduce all scores in the measures of anxiety used, except the physiological measure of Hearth Beat Frequency that showed little change. The participant's verbal reports were taken regularly throughout the study and indicated that the therapy helped them to achieve important improvement in the quality of academic and social life.